Migration management, capacity building and the sovereignty of an African State: International Organization for Migration in Djibouti. - Dini, Sabine (Journal of Ethnic & Migration Studies, 2018)
This article analyses the activities of the International Organization for Migration (IOM) in Djibouti, and especially its capacity-building activities in the field of migration management. It ethnographically documents how these projects transform state sovereignty. It argues that this is done not only through the Djiboutian government's increased capacity to exclude undocumented migrants, but also through the renewed governance of the entry of national-citizens into the state territory. IOM's projects institutionalise a state of exception (Agamben) that produces both legitimate political authority and national citizenship in the receiving State. Such institutionalisation is finally embedded within an international mobility regime characterised by a 'sedentarist' narrative, targeting specifically African citizenship.